2001
DOI: 10.1021/cm000949k
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the Polymer Electrolyte Complexes PEO6:LiXF6 (X = P, Sb), Determined from Neutron Powder Diffraction Data

Abstract: The crystal structures of the polymer electrolyte complexes PEO6:LiPF6 and PEO6:LiSbF6 have been obtained from powder diffraction data collected from deuterated molecules on the OSIRIS neutron powder diffractometer at ISIS, Rutherford Appleton Laboratory. The structures are similar to that recently reported for the PEO6:LiAsF6 complex and consist of rows of Li+ ions encapsulated within columns formed by pairs of nonhelical PEO chains. The Li+ ion is coordinated by five ether oxygens. The anions reside between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
154
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(161 citation statements)
references
References 12 publications
7
154
0
Order By: Relevance
“…[28][29][30] This is more or less in agreement with our DSC results which give 48% for amorphous polymer. Since the presence of salt may influence the crystal formation of PEO as has been observed by other groups in the past 35,36 we believe that discrepancies between the 45% calculated from literature and the 48% from our DSC data may result from the presence of salt. At the same time, examining the DSC traces shown in Fig.…”
Section: Resultssupporting
confidence: 59%
“…[28][29][30] This is more or less in agreement with our DSC results which give 48% for amorphous polymer. Since the presence of salt may influence the crystal formation of PEO as has been observed by other groups in the past 35,36 we believe that discrepancies between the 45% calculated from literature and the 48% from our DSC data may result from the presence of salt. At the same time, examining the DSC traces shown in Fig.…”
Section: Resultssupporting
confidence: 59%
“…These models are constructed from the structures in (PEO) 6 :LiAsF 6 , (PEO) 6 :LiPF 6 and (PEO) 6 :LiSbF 6 polymer-salt complexes, i.e. electrolytes, which have been solved ab-initio from X-ray diffraction data recently 28,29 . The reason why we have chosen these structures among variety of PEO-salt complexes is that the conformation of PEO chains within the crystal unit cell for these three models belongs to P2 1 /a space group, quite similar to the distorted D 7 space group between the resonant and non-resonant emission spectra for oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…[19] In such coordinate structures, the PEO chains have never been found to adopt the all-trans conformation sequence. The computer simulation showed that as table coordinate structure can not be achieved between the Li + ions and the EO segmentsint he alltrans conformation.…”
Section: Fnmr Reveals That the Motions Of LImentioning
confidence: 99%
“…If considering the significant change in the mobility of the Li + in the same temperature range (see Figure 3b and the relatedd iscussion), the 19 …”
mentioning
confidence: 96%
See 1 more Smart Citation